Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian - Nuuru Rizky Ammalia; Supriyono Supriyono (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of product quality and price perceptions on Samsung Smartphone purchasing decisions. This research method is descriptive quantitative. The research population was taken from East Java "Veteran" UPN Faculty of Economics and Business students who used Samsung smartphones. Samples or research respondents were taken by means of non-probability sampling through accidental sampling, and a sample of 66 people was obtained. The research data is in the form of primary data obtained from the answers of respondents who filled out the questionnaire, and secondary data in the form of Samsung Smartphone sales data for two years (2020-2021). The analysis used is Partial Least Square (PLS). The results showed that product quality on purchasing decisions has a path coefficients value of 0.362610, and a T-statistic value of 4.002994 > 1.96 (0.05), meaning that the significance is positive; b) price perception on purchasing decisions has a path coefficients value of 0.578573, and a T-statistic value of 7.394289 > 1.96 (0.05), meaning that the significance is positive. In conclusion, the better the quality of a Samsung Smartphone product and the perception of price, the better the influence on Samsung Smartphone purchasing decisions. Keywords: Product Quality, Purchase Decision, Perceived Price